2006
DOI: 10.1038/nature04367
|View full text |Cite|
|
Sign up to set email alerts
|

A brain-specific microRNA regulates dendritic spine development

Abstract: MicroRNAs are small, non-coding RNAs that control the translation of target messenger RNAs, thereby regulating critical aspects of plant and animal development. In the mammalian nervous system, the spatiotemporal control of mRNA translation has an important role in synaptic development and plasticity. Although a number of microRNAs have been isolated from the mammalian brain, neither the specific microRNAs that regulate synapse function nor their target mRNAs have been identified. Here we show that a brain-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
1,444
2
11

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,663 publications
(1,491 citation statements)
references
References 43 publications
34
1,444
2
11
Order By: Relevance
“…Such changes are indicated by an increase in red color as development proceeds. This agrees with the hypothesis that miRNAs play an important role in differentiation and development (Chen et al, 2005;Wienholds et al, 2005;Giraldez et al, 2006;Naguibneva et al, 2006;Schratt et al, 2006;Voorhoeve et al, 2006). The one notable exception to relatively limited expression of miRNAs during early development is the pattern observed at sphere stage embryos where there appears to be significantly greater expression compared to other early time points (Fig.…”
Section: Developmental Expression Of Mirnassupporting
confidence: 89%
“…Such changes are indicated by an increase in red color as development proceeds. This agrees with the hypothesis that miRNAs play an important role in differentiation and development (Chen et al, 2005;Wienholds et al, 2005;Giraldez et al, 2006;Naguibneva et al, 2006;Schratt et al, 2006;Voorhoeve et al, 2006). The one notable exception to relatively limited expression of miRNAs during early development is the pattern observed at sphere stage embryos where there appears to be significantly greater expression compared to other early time points (Fig.…”
Section: Developmental Expression Of Mirnassupporting
confidence: 89%
“…It has been shown previously that LIMK1 deletion results in smaller spine heads, and LIMK1 overexpression blocks NMDA‐induced shrinkage of dendritic spines (Meng et al , 2002; Calabrese et al , 2014), suggesting that LIMK1 plays an important role in maintaining spine size, or restricting spine shrinkage. A previous report demonstrated that endogenous LIMK1 protein expression is down‐regulated by miR‐134 in neurons (Schratt et al , 2006), and our luciferase reporter assay results suggest that LIMK1 translation is regulated by an NMDAR‐dependent mechanism that involves Ago2 phosphorylation at S387. We therefore hypothesised that increased RISC activity caused by Ago2 phosphorylation at S387 is involved in NMDA‐stimulated spine shrinkage via translational repression of LIMK1.…”
Section: Resultssupporting
confidence: 71%
“…We analysed two dendritically regulated UTRs; LIMK1 , which is regulated by miR‐134 (Schratt et al , 2006), and APT1 , which is regulated by miR‐138 (Siegel et al , 2009). Both of these miRNAs have been shown previously to regulate dendritic spine morphology (Schratt et al , 2006; Siegel et al , 2009), and we previously demonstrated that NMDAR activation increased translational repression of the LIMK1 reporter via miR‐134 and of the APT1 reporter via miR‐138 within 10 min after stimulation (Antoniou et al , 2014; Rajgor et al , 2017). Knockdown of Ago2 by shRNA caused a dramatic increase in expression of both reporter constructs, consistent with a deficit of miRNA‐mediated translational repression, and NMDAR stimulation had no effect under these conditions (Fig 5A and B).…”
Section: Resultsmentioning
confidence: 99%
“…Reversible silencing may be of particular importance in cells such as neurons, where localized translation at dendritic spines responds to synaptic stimulation [27]; and requires that target mRNAs are repressed translationally, without major mRNA decay as reported [24][25][26]. This apparent discrepancy may be explained by mechanistic differences between different cell types and/or miRNAs investigated, or by the presence of regulatory factors that modulate the miRNA effects in a target-specific way.…”
Section: Translational Inhibition Precedes Poly(a) Tail Shorteningmentioning
confidence: 99%
“…A unifying model for miRNA-mediated repression While genome-wide studies proposed that miRNA-mediated repression mainly leads to mRNA decay at steady state [7][8][9][10], other reports describe situations in which it can be rapidly reversed in response to different cellular cues [24][25][26]. Reversible silencing may be of particular importance in cells such as neurons, where localized translation at dendritic spines responds to synaptic stimulation [27]; and requires that target mRNAs are repressed translationally, without major mRNA decay as reported [24][25][26].…”
Section: Translational Inhibition Precedes Poly(a) Tail Shorteningmentioning
confidence: 99%